Analysis of CNT electronics structure to design CNTFET - Farhana, Soheli; Alam, A. H. M. Zahirul; Motakabber, S. M. A.; Khan, Sheroz (2013)
In this paper, graphene electronic structure of carbon nanotubes has been analyzed and validate with past theoretical and experimental results. The energy dispersion relation, effective mass and intrinsic carrier concentration of graphene have been analyzed to build diverse carbon nanotubes. The electronics properties of graphene are subject to change with the different diameters and wrapping angles of carbon nanotubes. Different chiral vector (n, m) of a graphene allows to design carbon nanotube for a wide range of applications, which can be achieved from the analyzed carrier concentration calculation. The proposed calculations set a higher boundary for a wide range of applications including the integration of carbon nanotube internal architecture and carbon nanotube field effect transistors.